The Influence of Depression on Biased Diagnosis of Premenstrual Syndrome and Premenstrual Dysphoric Disorder by the PSST Inventory - Andrzej Śliwerski; Karolina Koszałkowska (Life, 2021)
The diagnosis of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) poses a challenge for clinicians due to the overdiagnosis of retrospective methods and overlapping symptoms with depression. The present study utilized an Item Response Theory analysis to examine the predictive utility of the Premenstrual Symptom Screening Tool (PSST) in women with and without depression. Two hundred and fifteen women aged 20–35 completed the PSST, a daily symptom calendar, SCID-I, and CES-D for two consecutive menstrual cycles. PSST items: fatigue, depressed mood, feeling overwhelmed, anxiety/tension, and decreased interest in everyday activities were the best predictors of PMS. Unlike the daily symptom ratings, the PSST over-diagnosed PMS/PMDD in the depressed group but not in the group of women without PMS/PMDD. While diagnosing premenstrual disorders, clinicians should be aware that a retrospective diagnosis with PSST can be more sensitive to mood disorders and cycle phases than a prospective diagnosis with a daily symptoms calendar.